PLENIPOTENTIARY REPRESENTATIVES WITHOUT MANDATES": THE SOVIET EMPLOYEES OF SAG/SDAG Wismut IN THE 1950s - Anna Barabanova (Гуманитарные и юридические исследования)
The article studies the problems of relationship between war and post-war generations of the USSR and the GDR. The relations developed between the employees of SAG/SDAG Wismut created to extract and enrich uranium ore for the Soviet nuclear project. The topicality of the problem is preconditioned by an opportunity to form a positive image of the USSR in the world. The Soviet specialists that were sent to work SAG/SDAG Wismut became members of a team created from representatives of the two countries that had just completed a bloody war. Both on production and at home they represented the cultural traditions of their country. Therefore, they inevitably acquired the status of actors of cultural diplomacy. The research tasks were implemented on the basis of a set of documents. Those were the documents about the Soviet atomic project and the creation of SAG/SDAG Wismut, as well as memoirs of Soviet and German SAG/SDAG Wismut employees. The microanalysis allowed to specify and systematize memories as wekk as view them in a broader social context. The study made it possible to conclude that for many months and many years Soviet geologists, engineers and other technical workers lived and worked in a social space that was not only foreign, but also hostile. It was not easy to create an atmosphere of cooperation and friendship between the representatives of the two peoples, who were formerly deadly enemies. It is all the more surprising that they managed to create such atmosphere and the desired atom was doubly "peaceful".On the one hand, the creation of a Soviet atomic bomb was an important condition for preserving peace and preventing a new war, and on the other hand, work within the framework of the Atomic Project finally reconciled the postwar Soviet and the German youth, contributed to the creation of a positive image of the Soviet Union in Europe and in the world.